Metformin poisoning treated with high dose insulin dextrose therapy: a case series - Young, Theodore; Cevallos, Joaquim; Napier, James; Martin-Lazaro, Juan (Acta medica Lituanica, 2019)
Purpose. We describe the compassionate use of high dose insulin dextrose (HID) for life threatening metformin associated lactic acidosis (MALA) in four patients admitted to intensive care. Methods. Patients presenting with refractory lactic acidosis believed to be secondary to metformin poisoning were included. High dose insulin dextrose at 0.5units/kg/hour was infused in 50% dextrose. Frequent blood gas analysis allowed titration of therapy. All patients also received continuous veno-venous haemofiltration. Results. All four patients recovered to normal or near normal lactate and pH between 10 and 24 hours of therapy. Two patients had significant separation in time between initiation of HID and haemofiltration to suggest an independent effect of HID on improving pH and lactate. All patients had at least one episode of hypoglycaemia below 4.0 mmol/L with the lowest glucose in any patient during therapy being 3.0 mmol/L. All episodes were corrected with a dextrose infusion without sequelae. Conclusions. Our study demonstrates that HID therapy appears to be safe in patients with suspected metformin poisoning. It also appears to work to drive down lactate, improve pH and patients’ clinical condition. Further evidence is required to assess the effectiveness of HID therapy in the context of MALA.